Global Dynamics and Numerical Simulation of a Vaccinated Mathematical Model for Ebola Disease (Global Journal of Sciences, 2024)
Rabies continues to be a major hazard to public health around the world, especially in developing countries. This article proposes an equation that describes the mechanics of animal-to-animal transmission of rabies, accounting for vaccination and infected immigrants as potential preventative strategies. The effective reproduction number (R0) was computed using the next-generation matrix (NGM) Method. The Routh–Hurwitz Criterion was utilized to identify the disease-free equilibrium point (DFE). It was shown to be unstable in all other cases and to exhibit local asymptotic stability if (R0 < 1). It was also found that DFE is globally asymptotically stable and quadratic Lyapunov stable. Furthermore, the normalized forward sensitivity index approach and the central manifold theory for the bifurcation analysis were used to do a An examination of the model parameters’ sensitivity on the (R0). The simulation
Keywords: Ebola Disease; Stability analysis; Sensitivity analysis; Bifurcation analysis; and RK-4 method